METODE OUTDOOR STUDY BERMEDIA POP-UP BOOK DALAM PEMBELAJARAN IPA SISWA TUNAGRAHITA - PUSPITASARI, DESI (Jurnal Pendidikan Khusus, 2015)
ABSTRACT   Learning science was a process to give experience to learners about natural phenomenon or natural symptoms. Mentally retardation children had intellectual disorder which affected to the learning problem such as they were hard to think abstractly, anything to learn should be concrete. Therefore, to solve the learning problem of mentally retardation children about learning science it had been applied outdoor study method with pop-up book media. This research had purpose to analyze whether there was influence of outdoor study method with pop-up book media in learning science to mentally retardation children in SDLBN Sambirejo Nganjuk. . The research kind used was pre-experiment. The design used: one group pre test and post test. The method used to collect the data was test method. For the research data analysis it used analysis technique of statistic non parametric with sign test. From the result of data analysis it indicated that the pre test average value was 58,83 and the post test average value was 84,16. The research result after applying outdoor study method with pop-up book media indicated that zh = 2,05 > Zt = 1,96. It meant that “there was significant influence of outdoor study method with pop-up media in learning science to mentally retardation children in SDLBN Sambirejo Nganjuk.   Keywords: Learning science, outdoor study method, pop-up book